The role of phospholipase Cγ1 in breast cancer and its clinical significance. (September 2017) - Emmanouilidi, Aikaterini; Lattanzio, Rossano; Sala, Gianluca; Piantelli, Mauro; Falasca, Marco
Breast cancer, the most common malignancy among women, is usually detected at an early stage and has a low risk of relapse. Nevertheless, a significant number of patients cannot be cured solely by local treatment. Distinguishing between patients who are of low risk of relapse from those who are of high risk may have important implications to improve treatment outcomes. The PLC-γ1 signaling pathway promotes many physiological processes, including cell migration and invasion. Increasing evidence shows aberrant PLC-γ1 signaling implication in carcinogenesis including breast cancer. In this review, the role of PLC-γ1 in breast cancer and its clinical implications will be discussed, as well as its potential as a prognostic factor and a therapeutic target.